Odds, risks and appropriate diagnosis of gestational diabetes. Issue 6 (6th April 2015) - McIntyre, H David; Dyer, Alan R; Metzger, Boyd E
Summary: The International Association of the Diabetes and Pregnancy Study Groups (IADPSG) diagnostic process and criteria for gestational diabetes mellitus (GDM) have been recommended by the World Health Organization for adoption and were widely introduced into clinical practice in Australia from January 2015 — in Queensland, the Australian Capital Territory and variably across other states. The IADPSG criteria identify women at increased risk of a range of adverse pregnancy outcomes related to maternal hyperglycaemia. The relationship between maternal hyperglycaemia and adverse outcomes is continuous; however, one elevated glucose value is sufficient to impart a higher risk of pregnancy complications. We outline the background and statistical foundations of the IADPSG approach and refute the inference that invalid statistical reasoning underlies the IADPSG approach. The prevalence of GDM diagnosed by IADPSG criteria may be higher or lower than with other criteria, depending on the underlying population prevalence of fasting and post‐glucose load hyperglycaemia, which in turn vary with ethnicity. Studies comparing previous Australian criteria to the IADPSG criteria suggest GDM prevalence may decrease or may increase by up to 35% in specific populations with the planned change in criteria. Pregnancy complications have multiple potential underlying causes. No set of glucose criteria will ever be able to fully separate women and babies at risk of pregnancy complications from those who are not.